Integration of Islamic Values in Children's Collection Selection Criteria: A Case Study at Al Azhar 30 School Library in Bandung - Rachmelya Salsabila Firdausy; Angga Hadiapurwa; Suci Yanti Ramadhan (Universitas Wijaya Kusuma Surabaya, 2026)
Purpose Research: This study analyzes the collection development process at the Al Azhar 30 Islamic School Library, Bandung, using the Evans & Saponaro (2005) model. It specifically examines how Islamic values are integrated into selection criteria and how collaboration occurs between the sole librarian and teaching staff. Research Method: A qualitative single-case study was employed. Data were gathered through in-depth interviews with librarian, participant observation, and documentation. Analysis Data: Data were analyzed using the interactive model by Miles, Huberman, and Saldaña (2014). Results: The findings reveal that the selection process follows a systematic flow from needs analysis to evaluation. Islamic values act as a